Peaceful Mindset to Prevent Parenting Stress - Ratu, Bau; Septiwiharti, Dwi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
This study aims to provide an overview of parenting stress experienced by mothers. This research is a type of descriptive research with a quantitative approach. This study used a data collection tool in the form of Parenting Stress Index Short Form (PSI-short form). The subjects used in this study were mothers who live in various regions in Indonesia who were taken by simple random sampling. Data analysis in this study uses percentage techniques. The results obtained in this study describe the stress of parenting in the high category of 1.4%, the medium category of 38.02%, and the low category of 60.5%. Based on the results of the stress level, it shows that the majority of respondents are still able to control their response to the stressors they experience in parenting. Abstrak: Penelitian ini bertujuan memberikan gambaran mengenai stres pengasuhan yang dialami oleh para ibu. Penelitian ini merupakan jenis penelitian deskriptif dengan pendekatan kuantitatif. Penelitian ini menggunakan alat pengumpul data berupa Parenting Stress Index Short Form (PSI-short form). Subyek yang digunakan dalam penelitian ini adalah para ibu yang berdomisili diberbagai wilayah di Indonesia yang di ambil dengan cara simple random sampling. Analisis data dalam penelitian ini menggunakan teknik persentase. Hasil yang diperoleh dalam penelitian ini menggambarkan kondisi stres pengasuhan pada kategori tinggi sebesar 1,4%, kategori sedang 38,02%, dan kategori rendah 60,5%. Berdasarkan hasil tingkatan stres tersebut menunjukkan bahwa mayoritas responden masih dapat mengendalikan respon terhadap stressor dalam mengasuh anak yang dialaminya.